Structural analysis and anticomplement activity of a novel homogenous polysaccharide isolated from Juniperus tibetica kom. Issue 9 (22nd November 2019) - Li, Beibei; Xia, Long; Deji,; Zhu, Mengxia; Lu, Yan; Chen, Daofeng
Abstract: Juniperus tibetica Kom., a common forest species in Tibet, has been traditionally used in Tibetan medicine to treat rheumatic arthritis. In order to investigate the effective substances of J. tibetuca, anticomplent assay-guided fractionation using gradient anion-exchange chromatography and gel permeation chromatography was applied to the crude polysaccharides of the twigs and leaves of J. tibetica and led to the isolation of a homogenous polysaccharide, YB-PS. It exhibited a robust anticomplement activity (CH50 : 461 ± 10 μg/mL) through the classical pathway of complement system activation by targeting complement components C1q, C3, C4 and C5. The structure of YB-PS was studied by monosaccharide composition and methylation analyses, 1 D, 2 D NMR data and scanning electron microscope. The results indicated that YB-PS was composed of Ara, Gal, and Glc with a molar ratio of 5.8:3.0:1.2. Its backbone was comprised of 1, 3-linked α-Ara f, 1, 3, 5-linked α-Ara f, 1, 2, 4-linked α-Gal p, and 1, 3-linked α-Glc p with terminal α-Ara f, β-Gal p and 1, 4-linked β-Gal p as branches. YB-PS was found to have a sheet structure with smooth surface. This study provided scientific foundation for YB-PS as a potential complement inhibitor to treat diseases involved with excessive activation of the complement system. Graphical Abstract: